An Observational Study of Umbilical Cord Clamping and Care Practices during Home Deliveries in Central Uganda - Shakti, Divya; Singh, Veena; Nakigozi, Gertrude; Kiguli, Sarah; Kamat, Deepak (International Journal of Child Health and Nutrition, 2016)
Delayed umbilical cord clamping and care practices have important implications for infant iron stores and neonatal survival. This is especially important in countries like Uganda, where there is a high prevalence of anemia in women and children coupled with a high newborn mortality rate. This study assesses cord clamping and care practices in home births in a coverage area of 12 health centers in 4 districts near Kampala, Uganda. We interviewed 147 women, most of who had at least primary school education and delivered their babies in the homes of traditional birth attendants. Only 65% of the persons conducting delivery washed hands, and most wore gloves. Most frequent cord ties were threads (86.7%), and glove rims (8.3%). Cords were cut with clean instruments in most (93.1%) deliveries. During cord clamping, newborn was positioned at a higher level than mother in 59%, delayed clamping (≥3mins) was reported in 52%. Combination of delayed clamping and positioning of newborn at mother’s level or lower was reported in only 19%. Substances used for cord care included surgical spirit (42.4%), local herbs (24.5%), powder (22.6%), ash (21.6%), saline water (10.3%), and tea (2.8%). Cord care instructions given most commonly were: cleaning with warm saline water (27%), spirit or antiseptics (25%), and herb application (7%). Awareness regarding cord infections was poor (20%). Mother’s education level, and age were not associated with cord clamping or care practices. Our study indicates scope for interventions to help improve hemoglobin levels in infancy. Education regarding cord care practices may reduce infections.